Seaweed Potential in the Animal Feed: A Review - Morais, Tiago (2020)
Seaweed (known as marine algae) has a tradition of being part of the animal feed in the coastal areas, from ancient times. Seaweeds, are mixed with animal feed, because when consumed alone can have negative impact on animals. Thus, seaweeds are very rich in useful metabolites (pigments, carotenoids, phlorotannins, polyunsaturated fatty acids, agar, alginate and carrageenan) and minerals (iodine, zinc, sodium, calcium, manganese, iron, selenium), being considered as a natural source of additives that can substitute the antibiotic usage in various animals. In this review, we describe the nutritional values of seaweeds and the seaweed e ects in the seaweed-based animal feed/supplements.